DMM Outstanding Paper Prize 2021 winner: Daniel Bronder - Rachel Hackett (Disease Models & Mechanisms, 2022)
Disease Models & Mechanisms (DMM) is delighted to announce that the winner of the DMM Outstanding Paper Prize 2021 is Daniel Bronder, for his paper entitled ‘TP53 loss initiates chromosomal instability in fallopian tube epithelial cells’ ( Bronder et al., 2021). The prize of £1000 is awarded to the first author of the paper that is judged by the journal's editors to be the most outstanding contribution to the journal that year. To be considered for the prize, the first author must be a student or a postdoc of no more than 5 years standing.